The effect of internal branding on financial performance and brand loyalty with the mediating role of psychological empowerment (case study: Saman Bank, Tehran Province) - Nader Sheikholeslami Kandelousi; Samira Soltanieh; Fatemeh Ahmadi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The purpose of this research is to examine the effect of internal branding on financial performance and brand loyalty with the mediating role of psychological empowerment (case study: Saman Bank, Tehran Province).Methodology: This research is applied in terms of purpose and descriptive-survey in terms of method. The statistical population of the research includes all employees of Saman Bank in Tehran Province whose number is 1800 people. Cochran's limited population sampling formula is used to determine the required sample size. Based on Cochran's unlimited formula with 5% error, the sample number in this research is 317 people, which was selected by simple random method. In the current research, the field method was used to collect primary data, and the primary data collection tool was a five-option Likert questionnaire, and the library method was used to collect secondary data. The validity of the questionnaire was assessed using the method of content validity and face validity, and its reliability was calculated using Cronbach's alpha. Structural equation modelling method and SmartPLS software were used to test the research hypotheses.Findings: The results of the research showed that the effect of internal branding on financial performance and brand loyalty with the mediating role of psychological empowerment (case study: Saman Bank of Tehran Province) has a significant effect.Originality/Value: Originality in research mean what you are doing is from your own perspective although you may draw arguments from other research work to back up your arguments.